Internal Control System, Transparency, and Village Financial Management Accountability: Evidence From One Village in Indonesia - Suhartini, Ade; Budiman, Budiman; Hendarsyah, Decky; Junery, Muhammad Fadhil (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the influence of internal control systems and transparency on the accountability of village financial management. This type of research is quantitative and descriptive, using primary and secondary data. Data were collected using questionnaires and literature studies. The population was the Tanjung Datuk community and village officials, Siak Kecil sub-district, Bengkalis district, Riau. The sampling technique used was accidental sampling, with Yamane sample measurements, so the number of samples obtained was 237 people. The data analysis technique used multiple linear regressions with validity, reliability, classical assumptions and hypothesis testing using SPSS software. The results of this study indicate that the internal control system has a positive effect on the accountability of village financial management. However, transparency does not affect the accountability of village financial management. This study provides theoretical implications, especially in completing the theory regarding the influence of the internal control system on accountability and support for the theory of stewardship and legitimacy. This study can then be a reference for the village government in maintaining and improving the accountability of village financial management in implementing the internal control system.